The Online Advertising Tax A Digital Policy Innovation - Fuchs, Christian (CAMRI Policy Briefs, 2018)
"Google and Facebook currently control close to two-thirds of global advertising revenue. While dominating the online advertising market, these two companies have thus far avoided paying adequate taxes. This CAMRI policy brief presents a new policy innovation, the online advertising tax. Considering the key role of user activity and user data for the value of Google and Facebook's services, it explains how digital advertising companies' revenues could be taxed based on the respective country in which targeted users are located. The author reviews existing policy arguments and policy options and sets out practical steps to ensure that tax avoidance by online advertising companies is mitigated. Furthermore, he illustrates how tax revenues could be used to support public service internet platforms."